Astrocytes’ Contribution to Adult Neurogenesis in Physiology and Alzheimer’s Disease - Cassé, Frédéric; Richetin, Kevin; Toni, Nicolas (Frontiers in Cellular Neuroscience, 2018)
Adult neurogenesis is one of the most drastic forms of brain plasticity that occurs in the mature brain and there is a growing body of evidence showing that, in the hippocampus, this process contributes to brain plasticity and mechanisms of memory as well as depression. Interestingly, adult neurogenesis is tightly regulated by the neurogenic niche, which provides a structural and molecular scaffold for the growth, differentiation and functional integration of new neurons. In this review, we highlight the role of astrocytes in the regulation of adult neurogenesis in the context of cognitive function. We also discuss how the changes in astrocytes function may dysregulate adult neurogenesis and contribute to cognitive impairment in the context of Alzheimer’s disease.